2007
DOI: 10.1007/s00259-007-0480-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of multidrug resistance in an orthotopic model of osteosarcoma using 99mTc-sestamibi

Abstract: Purpose The purpose of this work was the development of an orthotopic model of osteosarcoma based on luciferaseexpressing tumour cells for the in vivo imaging of multidrug resistance (MDR) with 99m Tc-sestamibi. Methods Doxorubicin-sensitive (143B-luc + ) and resistant (MNNG/HOS-luc + ) osteosarcoma cell lines expressing different levels of P-glycoprotein and carrying a luciferase reporter gene were inoculated into the tibia of nude mice. Local tumour growth was monitored weekly by bioluminescence imaging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…To further deepen the understanding of the molecular antitumour action of BPC, we evaluated the effectiveness of this complex against tumour cells using in vitro and in vivo systems. These studies demonstrated that BPC is effective in vivo against a specific isogenic melanoma tumour model and shows Saos-2 cell cytotoxicity, which is an osteosarcoma cell line that presents high chemotherapy resistance properties [45] due to a p53 gene expression impairment [28,46] and ABC protein expression [47]. Part of the BPC cytotoxicity to Saos-2 cells was caused by the cytosolic calcium mobilisation, LMP and a pro-apoptotic protein Bax translocation with caspase-3 activation.…”
Section: Discussionmentioning
confidence: 98%
“…To further deepen the understanding of the molecular antitumour action of BPC, we evaluated the effectiveness of this complex against tumour cells using in vitro and in vivo systems. These studies demonstrated that BPC is effective in vivo against a specific isogenic melanoma tumour model and shows Saos-2 cell cytotoxicity, which is an osteosarcoma cell line that presents high chemotherapy resistance properties [45] due to a p53 gene expression impairment [28,46] and ABC protein expression [47]. Part of the BPC cytotoxicity to Saos-2 cells was caused by the cytosolic calcium mobilisation, LMP and a pro-apoptotic protein Bax translocation with caspase-3 activation.…”
Section: Discussionmentioning
confidence: 98%
“…However, 99m Tc-sestamibi is released much faster from thyroid than from parathyroid tissue, a pathophysiologic pattern possibly related to down-regulation in the parathyroid of the membrane-associated P-glycoprotein system related to multidrug resistance, a system for which 99m Tc-sestamibi is also a substrate. [58][59][60][61] This differential washout rate of 99m Tc-sestamibi from the thyroid relative to the parathyroid permits parathyroid scintigraphy to be performed with this single tracer, according to the so-called dual-phase 99m Tc-sestamibi acquisition protocol. As originally described by Taillefer et al, 54 planar imaging of the neck and thorax is acquired at 15 minutes, then 2-3 hours after the i.v.…”
Section: Parathyroid Scintigraphymentioning
confidence: 99%
“…6,20 Although several animal models of primary malignant bone tumors have been described, 3,5,8,9,19,23 there are no animal models of any primary malignant bone tumor in the spine; therefore, none of them addresses the sequence of events …”
mentioning
confidence: 99%